The Impact of Scale Direction on Data Quality - Ting Yan; Alexandru Cernat; Florian Keusch (Survey research methods, 2025)
Survey literature has documented a tendency for respondents to select scale options closer to the start of a scale, resulting in scale direction effects. This paper builds upon the literature and expands it in two important ways. First, we experimentally manipulated scale length, scale labeling, and scale type, and fully crossed them with scale direction. This experimental setup allows us to examine the moderating effects of other scale features on scale direction effects. Second, previous literature largely examined the impact of scale direction on distributional properties of answers. In this paper, we conducted a systematic assessment of reliability and validity of answers as well as measurement equivalence by scale direction, allowing us to gain a deeper understanding and a more complete picture of the impact of scale direction on resultant answers. The findings will have important implications for question writers and will provide practical guidance on the direction of scales.